The forecast of tomorrow: Exploring design strategies to develop a building withstanding future Swedish extreme weather - Mattsson, Johanna (My University, 2022)
As a consequence of climate changes, new or unusual weather conditions at unpredicted locations already affects our everyday life and destroy buildings and homes faster than predicted. However, we still construct our buildings according to previous climate situation. We must face the consequences of climate change and change the way we build to adapt to the “new normal” where extreme heat, extreme cold, storm and frequent rain- as well as dry periods most likely will become reality. Q1 - What extreme weather could occur in Sweden within 10-20 years? Q2 - How can a small house be constructed to withstand the consequences of the climate crisis concerning extreme weather in Sweden? Q3 - What impact would the findings to withstand future weather scenarios for a small house have on planning? Solutions for each forecast already exist, however there is a gap when the scale from extreme heat to extreme cold is a fact, particularly for northern countries. In this thesis a design proposal to withstand the negative consequences of climate change is developed. According to the IPCC reports, a realistic Swedish weather scenario is defined, and is the base when studying existing solutions of built references around the world for each criteria. Elements from the research phase is gathered as design strategies which in turn is translated and merged into a design proposal for four small residence buildings in a challenging urban area in Sweden. The site is handled as a microclimate aiming for self sufficiency. My ambition is to achieve a result of existing solutions merged into an experimental design proposal that could be useful as discussion material for planners, architects and private stakeholders who are interested in the development of constructions adapted to the consequences of the climate change.
Keywords: Climate change, Extreme weather, Design strategies, Swedish context, Microclimate